Estudio de factibilidad para la creación de un centro de atención infantil para hijos de madres estudiantes de educación media de las unidades educativas, cantón Quevdo, año 2015. - Alvarado Ponce, Denisse Paola (2016)
Research Project, prior to obtaining title Engineer in Business Management, está UN Aimed at Making feasibility study for the creation of the UN Children's Center para children of mothers Media Education Students Educational units Quevedo Canton. In which we proceeded to determine S. The problem for its development it could determine whether the proposed project is feasible four studies was conducted; market, technical, organizational and financial; That allowed collectively determine what if it's feasible S. UN create Child Care Center in Canton Quevedo. Also the methodology used, including the techniques, Applied Research Project Methods. The research results indicate that according to the demand for creation of the Child Care Centre paragraph children of mothers Students Media Education yields positive results para execution, where financing thereof shall be performed with a 100% by the Gadsden Municipal Quevedo Canton. The Economic Survey Economic and Financial Analysis of the research is detailed, they indicate that an initial investment of $ 80,230.00 is needed. For its operation, with respect to one the demand and supply is determined in the study, the UN This benefited generated by all social mothers who want to start working and find no UN Place to help control and guide their children, The child care center will provide professional services Paragraph reduce dropout rates and academic failure. Keywords: feasibility study, child care center, mothers high school students, educational units.